ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SD BERTINGKAT NAIKOTEN TERHADAP MATERI KERUANGAN YANG DIAJARKAN MENGGUNAKAN PETA - Glorya Mona Taunino; Tabani, Marie De Mondvort; Kewa Lamalelang , Klara D.; Eoh Ndolu , Tasya Gracya Belinda; Benu, Adam Bol Nifu; Musa, Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Special understanding is a fundamental ability that elementary school students need to develop as a foundation for recognizing their surrounding environment and understanding relationships among spatial elements such as location, direction, distance, distribution patterns, and spatial interconnections. In social studies (IPS) learning at the elementary level, spatial understanding is essential because it is closely related to geography content, which should be taught contextually and bassed on student's real enviroments. One strategic medium to develop spatial understanding is maps, as they provide concrete spatial representations that help students visualize geographic phenomena. However, many elementary students still experience difficulties in reading map symbols, understanding orientation, and identifying spatial realtionships. Similar condition were found at SD Negeri Bertingkat Naikoten, where maps have been used in learning, yet their contribution to students’ spatial understanding had not been clearly identified. This study aims to analyze the level of critical spatial thinking of fourth grade students at SD Bertingkat Naikoten in learning spatial material using maps. The research employed a descriptive quantitative method. The population consisted of all fouth grade students, with the sample being all students of class IV B. Data were collected trough classroom observation and written tests in the form of multiple choice and essay based on indicators of spatial critical thinking in map reading. The data were analyzed using descriptive statistic. The results show that most students achieved good to very good levels of spatial understanding. The dominance of these categories indicates that students were able to comprehend basic spatial concepts effetively trough map based learning. These findings suggest that help students organize and reason spatial information. Overall, the study confirms that the effective use of maps can significantly support the development of spatial thinking among elementary school students.